2012
DOI: 10.1007/s00464-012-2566-z
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric gastric band migration: erosion: an analysis of multicenter experience on 177 patients

Abstract: Background Laparoscopic adjustable gastric banding (LAGB) has proven to be a safe and effective surgical treatment for morbid obesity. It can be a simple, fast, reversible, anatomy-preserving procedure. Despite these advantages, its long-term efficacy came into question by the occurrence of complications such as intragastric band migration. Consistent information regarding this complication is still lacking. Treatment for migration is still being debated as well. Most of the inconsistencies of these data stem … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 39 publications
0
11
0
1
Order By: Relevance
“…The use of a silastic band or ring is very common in vertical gastroplasty or LAGB, and even in RYGB, and it may cause several complications, such as band slippage, gastric pouch outlet stenosis, and band erosion during its long-term placement around the upper stomach just below the EGJ. Among these complications, band erosion, the late process of intragastric band migration, may lead to loss of satiety, weight regain, and even infection at the port site, although most patients are asymptomatic [ 86 ]. The incidence of band erosion is variable and has been reported as 0.3%–1.9% among large-scale studies that included more than 100 patients, and a recent systemic review of 15,775 patients who underwent LAGB reported an overall incidence of 1.5% [ 87 ].…”
Section: Band Erosionmentioning
confidence: 99%
“…The use of a silastic band or ring is very common in vertical gastroplasty or LAGB, and even in RYGB, and it may cause several complications, such as band slippage, gastric pouch outlet stenosis, and band erosion during its long-term placement around the upper stomach just below the EGJ. Among these complications, band erosion, the late process of intragastric band migration, may lead to loss of satiety, weight regain, and even infection at the port site, although most patients are asymptomatic [ 86 ]. The incidence of band erosion is variable and has been reported as 0.3%–1.9% among large-scale studies that included more than 100 patients, and a recent systemic review of 15,775 patients who underwent LAGB reported an overall incidence of 1.5% [ 87 ].…”
Section: Band Erosionmentioning
confidence: 99%
“…The sensitivity of SSA for prediction of band migration is 60% (3/5) ( Table 2). about the optimal timing of migrated AGB removal [11,[15][16][17][18][19], many case reports have been issued describing serious complications arising from long standing band migration, including liver abscess [20], small bowel injury [21], delayed bleeding [22,23], and peritonitis [13,24]. One Group B patient in the present study also presented with acute peritonitis at 6 months after a diagnosis of SSA.…”
Section: Discussionmentioning
confidence: 55%
“…Gastric erosion and intragastric migration have been described previously as unusual complications that are commonly asymptomatic with no pathognomonic presentation [4]. The patient presentation is usually dependent on the extent of erosion and position of migration.…”
Section: Discussionmentioning
confidence: 98%